Zebrafish as a model for crystallin-associated congenital cataracts in humans - Rossen, Jennifer L.; Williams, Antionette L.; Bohnsack, Brenda L. (Frontiers in Cell and Developmental Biology, 2025)
Congenital cataracts are a leading cause of vision loss in children and can be an isolated finding or associated with systemic abnormalities. Isolated congenital cataracts are most commonly associated with pathogenic variants in one of the Crystallin genes. The α-Crystallins are small heat shock proteins that act as chaperones in the lens and other organs throughout the body to prevent protein aggregation and maintain tissue function. In contrast, the ß- and γ-Crystallins are structural proteins that are predominantly expressed in the mature lens and regulate its refractive index. However, the role of the Crystallins during lens development such that pathogenic variants result in inherited cataracts is less well-defined. As zebrafish allow real-time visualization of lens development, genetic manipulation of both the endogenous Crystallin genes as well as the use of transgenic overexpression of identified pathogenic variants yields important insight into the pathogenesis of congenital cataracts. Herein, we review the similarities and differences between human and zebrafish Crystallin genes. Further, we discuss the use of zebrafish as a model for congenital cataracts and explore the mechanisms that underlie the role of Crystallins in lens development. A better understanding of the genetic causes of congenital cataracts will lead to breakthroughs in preventing blindness from congenital cataracts and associated complications.